Association of placental and umbilical cord characteristics with cerebral palsy: national cohort study. (1st February 2023) - Ebbing, C.; Rasmussen, S.; Kessler, J.; Moster, D.
ABSTRACT: Objectives: Cerebral palsy (CP) is a group of movement disorders usually diagnosed in childhood. A substantial proportion are thought to be caused by antenatal events. Abnormalities of the umbilical cord and placenta are associated with an increased risk of adverse neonatal outcomes, but it is unclear whether these conditions also carry an increased risk of CP. We aimed to determine whether abnormalities of the umbilical cord or placenta are associated with CP and assess if these associations differ by sex of the child or gestational age at birth. Methods: We performed a national cohort study by linking data from The Medical Birth Registry of Norway with other national registries. All liveborn singletons born between 1999 and 2017 ( n = 1 087 486) were included and followed up until the end of 2019. Diagnoses of CP were provided by the Norwegian National Insurance Scheme and the Norwegian Patient Register. We used generalized estimating equations and multilevel log binomial regression to calculate relative risks (RR), adjusted for year of birth, and stratified analyses were carried out based on sex and gestational age at birth. Exposures were abnormal umbilical cord (velamentous or marginal insertion, single umbilical artery (SUA), knots and entanglement), and placental abnormalities (retained placenta, placental abruption and previa). Results: A total of 2443 cases with CP (59.8% males) were identified. Velamentous cord insertion (adjusted RR (aRR), 2.11 (95% CI, 1.65–2.60)), cord knots (aRR, 1.53 (95% CI, 1.15–2.04)) and placental abnormalities (placenta previa (aRR, 3.03 (95% CI, 2.00–4.61)), placental abruption (aRR, 10.63 (95% CI, 8.57–13.18)) and retained placenta (aRR, 1.71 (95% CI, 1.32–2.22))) carried an increased risk of CP. Velamentous cord insertion was associated with CP regardless of gestational age or sex. A retained placenta was associated with a 2‐fold increased risk for CP in males, while the associations of SUA and cord knot with CP were significant only among females. Conclusions: The detection of placental and umbilical cord abnormalities may help identify children at increased risk of CP. The associations between placental or umbilical cord abnormalities and the risk of CP do not vary substantially with gestational age at birth or sex of the child. © 2023 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.